Of Quintains, Harts, and Lionesses: Impure Melancholy As Shakespeare Liked It - Sean H. McDowell (Etudes Epistémè)
As You Like It is distinctive within the body of Shakespeare’s comedies in the assiduousness with which it systematically explores a single impure condition: melancholy, which enjoyed a vogue in popular entertainment during the last decade of Elizabeth I’s reign. The play centers on forms of interior pollution that together result in what Jaques describes as the corrupted “foul body of the th’infected world” that he would seek to “[c]leanse” through skillful raillery (2.7.59-61). Conventional scholarly wisdom identifies Jaques as the supreme melancholic not only in this play but in Shakespeare’s oeuvre as a whole. But Orlando’s volatility also can be attributed to another manifestation of melancholy, the result of “choler adust,” an overheating and hence corruption of one of his other humours. Rosalind, too, initially may be suffering from a third form, the so-called “green sickness,” as Gail Kern Paster has noted. By supplementing additional melancholic characters who showcase different manifestations, Shakespeare fully explores melancholy as a condition and as an experience, rather than simply apes the urban humoural comedies of George Chapman or Ben Jonson. Much of the play action derives from the collision of these variant melancholy types, and the play’s resolution hinges upon an affective cleansing of Orlando and Rosalind in their discovery of a newfound soulful love.